The Nature of Developing Social Competencies in Primary School (International Journal of Scientific Trends, 2025)
This article explores the essence and importance of developing social competencies among primary school students. It examines the roles of teachers, parents, and peers in this process. The author discusses the psychological, communicative, and emotional development of young students, highlighting the formative stages and the significance of games and social interaction in shaping social values and behavior.